4/5*75=60
ratio will be 24:36
2x+y=9
3x+5y=19
I will do this problem in 2 ways. I.)Substitution II.)Elimination
Solution I.) Substitution
We can subtract 2x from both sides in the first equation.
y=9-2x
Now we can substitute the y in the second equation with 9-2x
3x+5(9-2x)=19
-7x+45=19
-7x=-26
x=26/7
y=9-2(26/7)=11/7
Solution II.)Elimination
We can multiply both side of first equation by 5 to get a 5y in both equations.
10x+5y=45
Now because both are positive 5y we just need to do simple subtraction of the 2 equation, each side respectively.
(10x+5y)-(3x+5y)=45-19
7x=26
x=26/7
2*26/7+y=9
y=11/7
Ultimately you get the same answer, both are viable methods, some problems are faster with one method but I recommend mastering both since they are very useful.
Answer: C) as x → -∞, y → 3
as x→ ∞ , y → ∞
<u>Step-by-step explanation:</u>
see graph
Notice that as x approaches negative infinity (goes to the left), the y value approaches the asymptote of y = 3.
And as x approaches positive infinity (goes to the right), the y-value increases without bound so goes to infinity.
Answer:i dont think so
Step-by-step explanation:
12000 = 2x - 1500
12000 + 1500 = 2x
13500 = 2x
13500/2 = x
6750 = x <=== original price